The Possible Role of Plant Derived Essential Oils Against Fatigue in Post Acute Sequele Covid-19: A Literature Review Based on Evidence of Essential Oils on Fatigue - Satria, Fauzi; Widyawati, Tri; Rambe, Irfah Tut Alwiyah; Fitriani, Fitriani; Yusuf, Muhammad; Jamal, Monica Dwi (Fakultas Kedokteran Universitas Malikussaleh, 2023)
Symptoms of COVID-19 were found to be persistent after acute onset in some survivors. One of the Post Acute Sequele Covid-19 (PASC) problems is fatigue. Until now, the treatment options for fatigue in PASC are limited. Plant derived essential oils (EO) have been shown to reduce fatigue in several patient populations. The aim of this review is to present all the evidence regarding the benefits of plant derived EO for fatigue, whether they can be used as a therapy for fatigue associated PASC. Method: Literature search was conducted on the PubMed, Science Direct, Google Schoolar, and Springer Link databases focusing on the last 10 years randomized clinical trial (RCT) study on the topic of the effect of EO on fatigue with the keywords ˜Essential Oils, ˜Fatigue and ˜Long Covid-19. The evidence and other information obtained is then analyzed using PICO synthesis and presented in tabular and narrative form. Results: Based on the analysis of the 11 articles obtained, it was found that the utilization of plants EO such as Lavender, Sweet Orange; Lavender mixed Cananga, Juniper, and Rosemary; Sandalwood mixed Frankincense and Ravensara; Evening Primrose; leaves of Peppermint mixed Black Pepper, Clove Bud, White Grapefruit and Bergamot have been shown to reduce fatigue in several patient populations compared to control group. Conclusion: Plant derived EO may have a role and be useful for reducing fatigue in PASC.